The Effect of Toxic Friendship on Students' Mental Health - Esperansa, Serafina Trixi; Siva, Nur; Putri Saraswati , Ida Ayu; Wisnawa, Kadek Sukma Cahyani; Kistian, Agus (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2023)
This study aims to investigate the influence of toxic friendships on students' mental well-being. Specifically, it examines the detrimental effects of negative relationships within friendships on individuals' mental states. The research focuses on students enrolled in the Communication Science Study Program at Mercu Buana University Yogyakarta, Class of 2021. A sample of 135 students was selected using a simple random sampling technique from a population of 226. This type of research is quantitative research with a survey method approach. This study employing a modified questionnaire titled